2016
DOI: 10.1093/imanum/drw039
|View full text |Cite
|
Sign up to set email alerts
|

Fast and accurate computation of Chebyshev coefficients in the complex plane

Abstract: Chebyshev expansion coefficients can be computed efficiently by using the FFT, and for smooth functions the resulting approximation is close to optimal, with computations that are numerically stable. Given sufficiently accurate function samples, the Chebyshev expansion coefficients can be computed to machine precision accuracy. However, the accuracy is only with respect to absolute error, and this implies that very small expansion coefficients typically have very large relative error. Upon differentiating a Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 28 publications
(53 reference statements)
0
10
0
Order By: Relevance
“…Optimal here entails selection of r * (n) such that round-off error is minimised during numerical work. The recent work of [85] extends this analysis to the case of Chebyshev expansion coefficients which may be considered to be embedded as the Taylor coefficients of a particular integral transformation there described. As a preliminary, define the Bernstein ellipse Γ E with foci at ±1 and major and minor semi-axis lengths summing to the "radius" parameter r B :…”
Section: Complex Analytic Toolsmentioning
confidence: 99%
See 3 more Smart Citations
“…Optimal here entails selection of r * (n) such that round-off error is minimised during numerical work. The recent work of [85] extends this analysis to the case of Chebyshev expansion coefficients which may be considered to be embedded as the Taylor coefficients of a particular integral transformation there described. As a preliminary, define the Bernstein ellipse Γ E with foci at ±1 and major and minor semi-axis lengths summing to the "radius" parameter r B :…”
Section: Complex Analytic Toolsmentioning
confidence: 99%
“…In complete analogy to [9] the absolute and relative stability of the above approximation are then considered by [85]. It is shown that evaluation of the Chebyshev coefficients is absolutely stable.…”
Section: Complex Analytic Toolsmentioning
confidence: 99%
See 2 more Smart Citations
“…Analytic continuation in a region bounded by an ellipse is mentioned as Example 3 of [12], and a detailed analysis of algorithms in this geometry is presented in [7]. Results for ellipses analogous to those of [5] for disks can be found in [28].…”
Section: Analytic Continuation In Chebfunmentioning
confidence: 99%